Preparation and characterization of powdered activated carbon from empty fruit bunch - Ameen, E. S. M.; Muyibi, Suleyman Aremu; Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed; Abdul Karim, Mohd Ismail (IWA publishing, 2010)
Different powdered activated carbon (PAC) samples were prepared from oil palm industrial residue namely empty fruit bunch (EFB). The prepared EFB samples were carbonized and activated in a horizontal furnace. Physical activation consisted of carbonization for 30 minutes using nitrogen gas followed by activation with CO2 gas at different flow rates, temperature and time were used to optimize production conditions. The PAC samples produced were investigated through adsorption study using phenol aqueous solution of 50 mg/L concentration. Characterizations of the best quality PAC samples produced were determined. The result of this work demonstrated that activation temperature had significant effect on the adsorption properties of the activated carbons. The PAC produced at activation temperature of 800oC, CO2 gas flow rate of 0.1 L/min and activation time of 15 minutes proved to be the best quality adsorbent as it had given 95.54% of phenol removal at initial 15 minutes contact time. Characterization of EFB based-PAC showed good quality adsorbent with highly active sites and well-developed pores with BET surface area of 374.37 m2/g. The experimental results indicated that the activated carbon prepared from EFB is a promising product in industrial applications as well in water and wastewater treatment.